The Circadian Molecular Machinery in CNS Cells: A Fine Tuner of Neuronal and Glial Activity With Space/Time Resolution - Fagiani, Francesca; Baronchelli, Eva; Pittaluga, Anna; Pedrini, Edoardo; Scacchi, Chiara; Govoni, Stefano; Lanni, Cristina (Frontiers in Molecular Neuroscience, 2022)
The circadian molecular machinery is a fine timekeeper with the capacity to harmonize physiological and behavioral processes with the external environment. This tight-knit regulation is coordinated by multiple cellular clocks across the body. In this review, we focus our attention on the molecular mechanisms regulated by the clock in different brain areas and within different cells of the central nervous system. Further, we discuss evidence regarding the role of circadian rhythms in the regulation of neuronal activity and neurotransmitter systems. Not only neurons, but also astrocytes and microglia actively participate in the maintenance of timekeeping within the brain, and the diffusion of circadian information among these cells is fine-tuned by neurotransmitters (e.g. dopamine, serotonin and γ-amino butyric acid), thus impacting on the core clock machinery. The bidirectional interplay between neurotransmitters and the circadian clockwork is fundamental in maintaining accuracy and precision in daily timekeeping throughout different brain areas. Deepening the knowledge of these correlations allows to define the basis of drug-interventions to restore circadian rhythms, as well as to predict the onset of drug treatment/side effects that might promote daily desynchronization. Furthermore, it may lead to a deeper understanding of the potential impacts of modulations in rhythmic activities on the pace of aging and provide an insight into the pathogenesis of psychiatric diseases and neurodegenerative disorders.